IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS (SDGS) THROUGH THE “KOTAKU” PROGRAM TO IMPROVE SANITATION EFFORT IN SUKABUMI CITY - Anisa Mawarni; Rizki Hegia Sampurna; M Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2024)
Proper Sanitation is one of the targets of SDGs Goals No. 6 where the availability of water and sanitation must be ensured. The provisions related to proper sanitation have been regulated in the Minister of Health Regulation (Permenkes) No. 3/2014 on Community-Based Total Sanitation. To participate in realizing and achieving Sustainable Development Goals (SDGs) target No.6, with the assistance of the Ditjen Cipta Karya, Kementrian Pekerjaan Umum dan Perumahan Rakyat, Sukabumi City Government has a KOTAKU Program with the aim of improving access to proper sanitation, the program target is 100-0-100, which means here is 100 percent universal access to drinking water, 0 percent of slum settlements, and 100 percent access to proper sanitation. The purpose of this study was to determine the implementation of Sustainable Development Goals (SDGs) through the "KOTAKU" program in an effort to improve proper sanitation in Sukabumi City. The research method was conducted using descriptive qualitative methods. In determining informants, snowball sampling technique was used, with data collection techniques including observation, interviews, documentation, audio-visual materials. The results of this study show that the Sustainable Development Goals (SDGs) Implementation program through the "KOTAKU" Program in an Effort to Improve Proper Sanitation in Sukabumi City has not yet reached the expected target due to limited resources both human resources and financial resources.